1976
DOI: 10.1111/j.1600-0447.1976.tb00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Gaze Aversion in Autistic and Normal Children

Abstract: Autistic children rarely engage in eye contact, and whilst observation suggests this is due to a specific avoidance of eye contact, some experimental studies have challenged this. In this study the effects on autistic and normal children of an adult looking at them with both eyes, with one eye covered, or apparently not looking at them (both eyes covered) were investigated. As expected, autistic children looked more at the adult with his eyes covered, and also engaged in less flight behaviour. They looked less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
6

Year Published

1978
1978
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 15 publications
0
32
1
6
Order By: Relevance
“…almost exclusively fixated the mouth during conversations is also consistent with this hypothesis. However, it is important to note that autism likely involves an active aversion to fixating the eyes (Hutt and Ounsted, 1966;Richer and Coss, 1976;Spezio et al, 2007), whereas we do not have any evidence of direct gaze aversion in S.M. Instead, our observations to date strongly suggest that S.M.…”
Section: Discussioncontrasting
confidence: 62%
“…almost exclusively fixated the mouth during conversations is also consistent with this hypothesis. However, it is important to note that autism likely involves an active aversion to fixating the eyes (Hutt and Ounsted, 1966;Richer and Coss, 1976;Spezio et al, 2007), whereas we do not have any evidence of direct gaze aversion in S.M. Instead, our observations to date strongly suggest that S.M.…”
Section: Discussioncontrasting
confidence: 62%
“…Two-not mutually exclusive-explanations have been highlighted in the literature. First, previous research suggested that eye contact might be aversive (Hutt and Ounsted, 1966;Richer and Coss, 1976;Kylliäinen and Hietanen, 2006), grounded on behavioral and psychophysiological findings (Joseph et al, 2008). A previous study using the same paradigm, furthermore, showed a strong increase in gaze away from the eyes when starting fixation on the eyes compared with controls .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research highlighted two potential explanations: one hypothesis suggests a general lack of social attention, resulting in a missing orientation toward social cues, such as the eyes (Dawson et al, 1998;Grelotti et al, 2002;Schultz, 2005;Neumann et al, 2006). Another hypothesis suggests an aversiveness of eye contact, leading to an avoidance of eye fixation (Richer and Coss, 1976;Kylliäinen and Hietanen, 2006). In fact, these processes do not have to be mutually exclusive (Spezio et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the field of autism research, two distinctive models, the hyperarousal model and the hypoarousal model, have been developed based on the affective arousal model. The "hyperarousal model" states that the face and eyes of others are strongly aversive stimuli to individuals with ASD, and thus gaze avoidance is an adaptive response Coss, 1978;Dalton et al, 2005;Hutt & Ounsted, 1966;Joseph et al, 2008;Richer & Coss, 1976). Based on this model, some have even made a proposal such as "Teachers and nurses are recommended not to make efforts to engage autistic children even in friendly eye contact as this provokes more flight behaviour."…”
Section: Two Variants Of the Affective Arousal Modelmentioning
confidence: 99%
“…Hutt & Ounsted, 1966), particularly when the eyes in the face are visible (e.g. Coss, 1978;Richer & Coss, 1976). However, as other concurrent studies failed to replicate gaze avoidance (e.g.…”
Section: Behavioural Studies Before Mid 1990smentioning
confidence: 99%